Pengukuran Kualitas Website Filkom Apps Mahasiswa Universitas Brawijaya Dengan Menggunakan Metode Webqual 4.0 dan Importance and Performance Analysis (IPA) - Masagus Hariadi Arief; Himawat Aryadita; Hanifah Muslimah Az-Zahra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
In the Faculty of Computer Science of Brawijaya Universitas there are web-based applications to support administrative processes that can connect between academic employees, lecturers and students in the work of student thesis known as Filkom apps website. As part of the quality assurance, the website needs to be evaluated in the service performance process. Webqual 4.0 is chosen as a method to evaluate the website where in the method there are four variables: usability, information quality, and service interaction quality, this method has the purpose to measure the quality of service at this time and the importance of each attribute in Webqual 4.0. The next method is IPA, which is used for conformity analysis, gap analysis, and IPA quadrant. The research data was obtained by distributing questionnaires to 90 respondents. The result of IPA quadrant analysis shows that there are four attributes that become the main priority in the improvement that is, ease to be operated, interaction with website is clear and understandable, precisely in arrangement of information layout, and website make easy to communicate with organization. Furthermore, there are three attributes that enter into the low priority in the improvement, such as attractive appearance, easy to navigate, and give space for personalization. The remaining attributes do not have improvement priorities because they belong to quadrants that have a service performance value to be sufficient to maintain or even have an excessive value.